Influence of salinity and storage on germination of Tamarix taxa with contrasted ecological requirements. (December 2016) - Terrones, Alejandro; Moreno, Joaquín; Agulló, Jonás C.; Villar, José L.; Vicente, Alicia; Alonso, M. Ángeles; Juan, Ana
Abstract: Tamarix typically appears in arid and semiarid habitats that are characterised by a broad spectrum of soil salinity. Scarce data are available about the influence of salt on seed germination. The aim of this paper is to analyse the influence of salinity and the loss of viability over time on seed germination of three western Mediterranean autochthonous Tamarix species ( Tamarix africana, Tamarix boveana and Tamarix gallica ) plus the eastern Mediterranean allochthonous Tamarix parviflora . These species appear in non-saline to hypersaline ecosystems. Germination percentage and mean-time germination were calculated. In general, germination was higher at no salinity, whereas higher salinities delayed germination. Seed germination of T. africana dramatically dropped at 1% salinity (from 23.7% to 4.1%), whereas for T. boveana and T. parviflora, germination decreased at 6% salinity (from 95% to 42% and from 89% to 14%, respectively), though T. boveana still retained a high germination percentage. Seeds of T. gallica showed intermediate behaviour and no germination was recorded for 6% salinity. Seed germination is also influenced by the storage time. After 3 months, germination values notably decreased to almost zero (from 70.6% to 0% for T. gallica and from 89% to 8% for T. parviflora ), except for T. africana . In the latter case, 1 month was enough to reduce germination values (from 23.7% to 2%). The observed germination differences match with their presence or absence in different semiarid damp environments and point at a dramatic loss of viability over time. Graphical abstract: Highlights: First data germination of Tamarix africana, Tamarix boveana, Tamarix gallica and Tamarix parviflora . Strong differences in germination among species of Tamarix under different salinities. Germination was higher at lower salinities whereas higher salinities delayed germination. Salt tolerance of seeds is related to the habitat where species usually grow. Tamarix seeds lose their viability after one to three months of storage.